G11 Tractography of the corpus callosum in Huntington disease. (29th August 2012) - Phillips, OR; Sanchez-Castaneda, C; Caltagirone, C; Di Pardo, A; Maglione, V; Squitieri, F; Sabatini, U; Di Paola, M
Abstract : Background: Recent diffusion tensor imaging (DTI) studies suggest that abnormalities in Huntington's disease (HD) extend to white matter (WM) tracts in early HD and even in presymptomatic (PreHD) stages. However, DTI tractography, which allows precise localisation of WM abnormalities has not yet been used to investigate changes associated with HD. Aims: The purpose of this study was to investigate whether the corpus callosum (CC) of PreHD subjects exhibit a measurable difference compared to healthy controls and HD patients in the Forceps Major (posterior projections) and Minor (frontal projections). Methods: All T1 and DTI data were acquired on a 3T Allegra MRI system (Siemens) for 33 healthy controls (22M/11F; age: 43.88±11.69), 19 PreHD subjects (13M/6F; age: 38.11±7.75) and 23 HD patients (13M/10F; age: 48.30±13.79). DTI scans were acquired with 30 directions and three acquisitions. The Forceps Major and Minor were delineated using predefined ROI's in TrackVis. The general linear model was used to compare tract volume with sex, age and CC volume included in the model. Results: Mean track volume for the FMajor: Controls=18.28±5.07, PreHD= 15.23±4.16, HD=13.98±4.16, and FMinor: Controls=14.90±4.21, PreHD=16.18±4.12, HD=11.60±4.08). Controls had a significantly larger FMajor compared to PreHD F[1, 51]=6.534, p<0.02 and PreHD subjects had a significantly larger FMajor compared to HD patients F[1, 42]=4.44, p <0.045. PreHD subjects had a significantly larger FMinor than HD Patients F[1, 42]=13.261, p<002. Conclusion: The results suggest there is a significant difference in posterior and frontal CC projections between PreHD subjects and HD patients indicating a volume reduction associated with disease progression. Furthermore, PreHD subjects exhibit significantly smaller posterior projections compared to healthy controls but no significant difference in frontal projections, signalling a posterior-to-anterior direction in disease progression.